Tuesday
March 28, 2017

Post a New Question

Posted by on .

Replace each equation with constants to complete the square and form a true equation
x^2+2x+--=(x+---)^2

  • algebra - ,

    how to do this: first, from the equation, we get b or the numerical coefficient of x.
    from the given, b = 2.
    then divide this by 2:
    2/2 = 1
    and square it:
    1^2 = 1
    thus, the number that we're looking for is 1:
    x^2 + 2x + 1 =(x + 1)^2

    hope this helps~ :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question